10 Gram-scale synthesis of TY-Phos ligand and its application in carbene insertion of Si-H bonds. (28th September 2022) - Zhang, Yaochen; Pan, Zhangjin; Guo, Hao; Yang, Junfeng; Zhang, Junliang
Graphical abstract: Abstract: The design of chiral ligands has always been one of the most prominent research areas in asymmetric catalysis. This method reports on the 10 g-scale synthesis of one class of Sadphos: TY-Phos ligand. The ligand preparation could be carried out on a scale of 10 g with a reasonable yield, and the preliminary exploration of its application in the enantioselective insertion of carbenes into Si−H bonds is reported.